FINANCIAL LEVERAGE AND PERFORMANCE OF LISTED FIRMS IN A FRONTIER MARKET: PANEL EVIDENCE FROM KENYA - Mule, Robert Kisavi; Mukras, Mohamed Suleiman (European Scientific Journal, ESJ, 2015)
This paper investigates the relationship between financial leverage and the financial performance of listed firm in Kenya. We use annual data for the period 2007 – 2011. Using various panel procedures, the study finds reasonably strong evidence that financial leverage significantly, and negatively, affects the performance of listed firms in Kenya (ROA, β = - .0438, p = .0350) and Tobin’s Q, β = -.5144, p = .0124). However, financial leverage negative but insignificant effect on ROE, β = -.0176, p = .5765). Unit root test results indicate: all the variables are integrated of order zero (p = .000). Second, because the performance of firms depends on other things than just their financial leverage, we control for the effects of those other variables by including them in our models. In this respect, the findings suggest that asset tangibility (β = .2302, p = .0215) and ownership concentration (β = -.0057 (p = .0353) are important determinants of performance measured in terms of Tobin’s Q. The study concludes that; that financial leverage is an important negative predictor of financial performance measured in terms of ROA and Tobin’s Q; ownership concentration is a pertinent negative predictor of financial performance measured in terms of Tobin’s Q and asset tangibility is a significant positive predictor of performance measured in terms of ROE and Tobin’s Q.